APMP INTERCOMPARISON OF DC VOLTAGE STANDARD AT NPSL ISLAMABAD (Biological Sciences - PJSIR, 2002)
Inter-comparison of DC voltage standards has now become the most suitable and authenticated means for maintaining the international tractability of national standards all over the world. The results of an intercomparison on DC voltage standards carried  out  at National  Physical  &  Standards Laboratory  (NPSL)  Islamabad  are  presented  and discussed.